JNSR 2019
DOI: 10.7176/jnsr/9-22-04
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Non-Timber Forest Products in Rural Communities’ Livelihoods around Chilimo Forest, West Shewa, Ethiopia

Abstract: In recent decades there has been growing interest in the contribution of non-timber forest products (NTFPs) for rural people livelihood improvement and poverty alleviation. However, as to the knowledge of the present researcher, limited studies have been done to analyze the role of non-timber forest products for rural livelihood diversification. Therefore, this study was conducted to identify main NTFPs used by local communities around Chilimo Forest. Furthermore, the study aimed to determine socioeconomic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…White pepper business contributed 40.7% to the overall income of producers in Njombe-Penja from January to December 2022. Similar results were obtained by Demie, [27] and suggests that NTFPs contribute significantly to household income and thus can act as a safety net during the period of hardship and other emergencies. This finding also implies that NTFPs constitutes an important component of the rural households' economy.…”
Section: Retailerssupporting
confidence: 86%
“…White pepper business contributed 40.7% to the overall income of producers in Njombe-Penja from January to December 2022. Similar results were obtained by Demie, [27] and suggests that NTFPs contribute significantly to household income and thus can act as a safety net during the period of hardship and other emergencies. This finding also implies that NTFPs constitutes an important component of the rural households' economy.…”
Section: Retailerssupporting
confidence: 86%
“…These are firewood, coffee, honey, fencing wood, tree fern (Seseno), charcoal, split wood (Gejo), stringer (Mager), Cardamom (Aframomum corrorima), climber, timber (Tawula), split wood for house wall construction (Filit), mortar, plough, yoke, pestle and bamboo. All of the sample households are engaged in collection of forest products and it is similar to the earlier finding in the study area and Chilimo forest, Ethiopia (Mullatu, 2010;Demie, 2019). This engagement of communities in forest product collection is more than the findings of studies in Bench Maji zone and Yayo district of Ethiopia (Chanie andYirsaw, 2018, Asfaw andEtefa, 2017).…”
Section: Forest Product and Its Contribution Major Forest Product Col...supporting
confidence: 81%
“…It is reported that the more isolated and remotely located the area is, the higher is the contribution of NTFPs to noncash income [5]. The economic, livelihood, and ecological benefits of NTFPs can only be realized when their collectors are benefitted fully [5,12,13,17].…”
Section: Socioeconomic Attributesmentioning
confidence: 99%
“…NTFPs provide natural insurance against hunger and malnutrition during scarcity and even during famines [5]. NTFPs are thus vital for the social development of the indigenous/forest fringe and rural communities [17]. In spite of the "right of ownership, i.e., access to collect, use and dispose of minor forest produce by the 'Forest Rights Act, 2006'" to the indigenous communities dependent on forest or forest dwellers, they still remain underprivileged and impoverished [18].…”
Section: Introductionmentioning
confidence: 99%